TP53 minigene analysis of 161 sequence changes provides evidence for role of spatial constraint and regulatory elements on variant-induced splicing impact - Daffodil M. Canson; Inés Llinares-Burguet; Cristina Fortuno; Lara Sanoguera-Miralles; Elena Bueno-Martínez; Miguel de la Hoya; Amanda B. Spurdle; Eladio A. Velasco-Sampedro (npj Genomic Medicine)
Abstract We investigated the role of TP53 splicing regulatory elements (SREs) using exons 3 and 6 and their downstream introns as models. Minigene microdeletion assays revealed four SRE-rich intervals: c.573_598, c.618_641, c.653_669 and c.672+14_672 + 36. A diagnostically reported deletion c.655_670del, overlapping an SRE-rich interval, induced an in-frame transcript Δ(E6q21) from new donor site usage. Deletion of at least four intron 6 G-runs led to 100% aberrant transcript expression. Additionally, assay results suggested a donor-to-branchpoint distance <50 nt for complete splicing aberration due to spatial constraint, and >75 nt for low risk of splicing abnormality. Overall, splicing data for 134 single nucleotide variants (SNVs) and 27 deletions in TP53 demonstrated that SRE-disrupting SNVs have weak splicing impact (up to 26% exon skipping), while deletions spanning multiple SREs have profound splicing effects. Our findings may prove relevant for identifying novel germline TP53 variants causing hereditary cancer predisposition and/or somatic variants contributing to tumorigenesis.